PENGARUH KEPEMIMPINAN, MOTIVASI, DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN DI HOTEL RAFFLES JAKARTA - Julian Wisnu Putra Perdana; Darwin Raja Unggul Saragih (LPPM Universitas Asa Indonesia, 2019)
Purpose- This research aims is to analyze the influence of leadership, motivation and communication to empeloyee’s performance. Design/methology/approach The research done in Raffles Hotel Jakarta by distributing questionairs to 100 respondents, bu purposive sampling method. Analysis method used is multiple regression and its requirements . Findings- Based on the analysis, it can be concluded that, there is a weak but real effect of leadership on employee’s performance with a contribution of 8.58%. There is a moderate but real influence of motivation on empeloyee’s performance with contribution equal to 17,38%. There is a strong and real influence of communication on empeloyee’s performance with contribution equal to 61,93%. If the variables are combined together it is found that there is a very strong positive influence of the three variables together to determine the empeloyee’s performance with a contribution of 81,18%, where other factors are influential but not discussed in this research that is equal to 18,98%.